Surgical Outcomes After Apical Repair for Vault Compared With Uterovaginal Prolapse. Issue 6 (June 2018) - Rogers, Rebecca G.; Nolen, Tracy L.; Weidner, Alison C.; Richter, Holly E.; Jelovsek, J. Eric; Shepherd, Jonathan P.; Harvie, Heidi S.; Brubaker, Linda; Menefee, Shawn A.; Myers, Deborah; Hsu, Yvonne; Schaffer, Joseph I.; et al.
Abstract : (Abstracted from Obstet Gynecol 2018;131:475–483) The incidence of posthysterectomy prolapse ranges from 6% to 8%. Many surgeons treat posthysterectomy or vault prolapse differently than uterovaginal prolapse in women planning to undergo surgery for apical pelvic organ prolapse (POP), because they believe that a previous hysterectomy increases both risk of prolapse recurrence and adverse events.